2019
DOI: 10.1111/ina.12583
|View full text |Cite
|
Sign up to set email alerts
|

Home and day‐care microenvironment exposure to Blomia tropicalis allergens and their associations with salivary eosinophilic cationic protein (ECP) among preschool children in Singapore

Abstract: To date, exposure studies linking dust-mite allergens with asthma and allergic morbidities have typically relied on sampling from representative locations in the home for exposure assessment. We determine the effects of differing microenvironments allergen exposures on asthma and asthma severity among 25 case and 31 control preschool children in Singapore. Blo t 5 allergen levels in various niches from the children's home and day-care microenvironments as well as their Blo t 5 time-weighted concentrations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…However, we did not find statistically significant difference ( P = .4) between occupant densities with indoor fine particle source contributions nor an increasing trend for increased contributions with occupant densities (Table 3). Plausible explanations could be that deposited particle levels are already low as the daycares are comprehensively cleaned on a daily basis 44 or particle levels attributed to day‐care center occupants’ activities are associated with larger particles 42,45 . In the former, Skullberg et al 45 reported lower concentrations of airborne particles greater than 5 μm in offices that were thoroughly cleaned.…”
Section: Resultsmentioning
confidence: 99%
“…However, we did not find statistically significant difference ( P = .4) between occupant densities with indoor fine particle source contributions nor an increasing trend for increased contributions with occupant densities (Table 3). Plausible explanations could be that deposited particle levels are already low as the daycares are comprehensively cleaned on a daily basis 44 or particle levels attributed to day‐care center occupants’ activities are associated with larger particles 42,45 . In the former, Skullberg et al 45 reported lower concentrations of airborne particles greater than 5 μm in offices that were thoroughly cleaned.…”
Section: Resultsmentioning
confidence: 99%